Differentiation among Young and Market-ready Cabernet Sauvignon, Pinotage and Shiraz Wines: Application of Canonical Discriminant Analysis using Flavonoid and Non-Flavonoid Compositional Data - Minnaar, P.P.; Booyse, M. (South African Journal of Enology and Viticulture, 2011)
Various factors affect the polyphenol compound concentrations of red grapes. These include cultivar, vineyard location, viticultural practices, microclimate, soil type and winemaking processes. Polyphenol compound concentrations of young and market-ready Cabernet Sauvignon, Pinotage and Shiraz wines were examined for the purpose of discrimination between grape cultivars. Thirty-five individual polyphenol compounds were quantified using a HPLC-DAD method. Stepwise discriminant analysis (SDA) was used to select a subset of discriminatory variables. In addition, data was grouped and investigated by canonical discriminant analysis, which showed that polyphenol concentrations can be used to discriminate among grape cultivars, young wines and market-ready wines. Flavonol, flavanol and anthocyanin patterns were used as a basis for differentiation of young wines, while flavanols and phenolic acids were used for differentiation of market-ready wines. Discriminant analysis performed at 95% significance level revealed a 100% categorisation of market-ready and young wines in terms of cultivar and 77.85% categorisation of a combination of market-ready and young wines in terms of grape cultivar. This illustrates the validity of polyphenols for studies pertaining to grape cultivar discrimination.